Transplanted Adult Neural Stem Cells Express Sonic Hedgehog In Vivo and Suppress White Matter Neuroinflammation after Experimental Traumatic Brain Injury - Genevieve M. Sullivan; Regina C. Armstrong (Stem Cells International)
Neural stem cells (NSCs) delivered intraventricularly may be therapeutic for diffuse white matter pathology after traumatic brain injury (TBI). To test this concept, NSCs isolated from adult mouse subventricular zone (SVZ) were transplanted into the lateral ventricle of adult mice at two weeks post-TBI followed by analysis at four weeks post-TBI. We examined sonic hedgehog (Shh) signaling as a candidate mechanism by which transplanted NSCs may regulate neuroregeneration and/or neuroinflammation responses of endogenous cells. Mouse fluorescent reporter lines were generated to enable in vivo genetic labeling of cells actively transcribing Shh or Gli1 after transplantation and/or TBI. Gli1 transcription is an effective readout for canonical Shh signaling. In ShhCreERT2;R26tdTomato mice, Shh was primarily expressed in neurons and was not upregulated in reactive astrocytes or microglia after TBI. Corroborating results in Gli1CreERT2;R26tdTomato mice demonstrated that Shh signaling was not upregulated in the corpus callosum, even after TBI or NSC transplantation. Transplanted NSCs expressed Shh in vivo but did not increase Gli1 labeling of host SVZ cells. Importantly, NSC transplantation significantly reduced reactive astrogliosis and microglial/macrophage activation in the corpus callosum after TBI. Therefore, intraventricular NSC transplantation after TBI significantly attenuated neuroinflammation, but did not activate host Shh signaling via Gli1 transcription.